Development Of Digital Marketing, Natural Dyeing, And Heating Machine Utilisation At Putri Kawung Bayat SMEs - Rahmawati, Rahmawati; Amperawati, Endang Dwi; Djuminah, Djuminah; Hartoko, Sri; Kurniasih, Lulus; Arifah, Siti (IMPOWERMENT SOCIETY, 2024)
This community service activity in Putri Kawung KUBE, Jarum Village, Bayat District, Klaten Regency aimed to enhance environmentally friendly production processes, IT-based marketing, institutional strengthening, and the adoption of appropriate technology to improve the quality of batik products with natural colors. The methods carried out in this service activity include: education about brand awareness and a number of business management skills such as financial management, marketable packaging and promotion; ppractice of environmentally friendly production processes with natural colours mixed with cow bone powder;adoption of TTG heating machines; pstrengthening diversification capacity both diversification of Klaten characteristic motifs and batik derivative products; p quality testing and quality certification of batik marks, especially for natural colour written batik products; TTG on the use of cow bone material in the natural dyeing process in order to improve the quality of anti-fade products ; and p information technology-based business management practices through digital marketing. The result of this activity is the increased knowledge of business actors in Putri Kawung KUBE in order to increase product innovation which in turn can encourage the optimisation of community income and economy in the Bayat area of Klaten Regency.The abstract contains a summary, introduction, problems, methods, results, and conclusions.